2009
DOI: 10.1007/s12272-009-2000-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cytotoxic evaluation of novel 2-(4-(2,2,2-trifluoroethoxy)-3-methylpyridin-2-ylthio)-1H-benzo[d]imidazole derivatives

Abstract: The present work deals with the anticancer effect of benzimidazole derivatives associated with the pyridine framework. By varying the functional group at N-terminal of the benzimidazole by different L-amino acids, several 2-(4-(2,2,2-trifluoroethoxy)-3-methylpyridin-2-ylthio)-1Hbenzo[d]imidazole derivatives 9(a-j) were synthesized. Their chemical structures were confirmed by (1)H NMR, IR and mass spectroscopic techniques. The synthesized compounds were examined for their antiproliferative effects against human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…2-Heterocyclic benzimidazoles exhibit cytotoxic effects against a panel of human cancer cell lines (Refaat, 2010). Other derivatives are described as precursors of antileukemic agents (Ranganatha et al, 2009). Benzimidazole-4,7-diones show cytotoxicity against colon, breast and lung cancer cell lines (Gellis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…2-Heterocyclic benzimidazoles exhibit cytotoxic effects against a panel of human cancer cell lines (Refaat, 2010). Other derivatives are described as precursors of antileukemic agents (Ranganatha et al, 2009). Benzimidazole-4,7-diones show cytotoxicity against colon, breast and lung cancer cell lines (Gellis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The data showed that the electrospun nylon 6 nanofibers incorporated with biocides have lower IC 50 values compared to pristine electrospun nylon 6 nanofibers. Many studies have reported the cytotoxic effects of imidazole derivatives against various human cell lines . Assadieskandar et al considered their imidazole derivatives to be highly cytotoxic against various human cell lines with the following IC 50 values; HT‐29 (0.18 to >50 μM); MCF‐7 (0.40–22.90 μM); NIH‐3T3 (0.02 to >50 μM), and AGS (0.04–48.43 μM).…”
Section: Resultsmentioning
confidence: 99%
“…Assadieskandar et al considered their imidazole derivatives to be highly cytotoxic against various human cell lines with the following IC 50 values; HT‐29 (0.18 to >50 μM); MCF‐7 (0.40–22.90 μM); NIH‐3T3 (0.02 to >50 μM), and AGS (0.04–48.43 μM). The IC 50 values for imidazole derivatives against K562 (140–220 μM) and CEM cells (210–245 μM) were considered to be moderate . In comparison, the IC 50 values displayed by decImCHO (5.84 × 10 −5 μM) and Ag‐decImCH 2 OH (1.87 × 10 −5 μM) were significantly lower and could be considered to be potentially cytotoxic to the humans.…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of C]O stretch in the range of 1630e1600 cm À1 indicated the formation of tertiary amides (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) by the reaction of acid chlorides with the 4-(1H-benzoimidazol-2yl)-benzenesulfonic acid. The primary amino group in compound 1 is depicted by the presence of NH asymmetric stretch at 3481.81 cm À1 .…”
Section: Chemistrymentioning
confidence: 99%
“…Furthermore, the topological parameter, Balaban index (J) followed by the electronic parameter, LUMO and topological parameter, valence second order molecular connectivity index ( 2 c v ) is describing the antimicrobial activity of 4-[1-(substituted aryl/alkyl carbonyl)-benzoimidazol-2-yl]-benzenesulfonic acids (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Development Of Multi-target Qsar Modelmentioning
confidence: 99%